Crossing the Caucasus hunting for plants: the collection itinerary of the botanists Stéphen Sommier and Émile Levier in the summer of 1890 - Daniele Viciani; Lorella Dell’Olmo; Chiara Nepi; Lorenzo Lastrucci (Journal of Maps)
Stéphen Sommier and Émile Levier were eminent botanists and plant collectors (but also ethno-anthropologists, geographers and photographers), best known for their scientific travels in Italy and abroad. This study accurately reconstructs the travel and collection itineraries of a trip through the Caucasus in 1890. The botanical importance of this journey is significant, with over 10,000 specimens collected, more than 1600 taxa identified, and over 250 newly described taxa based on the collected samples. The locations visited are placed in a time sequence on up-to-date georeferenced topographic maps. Furthermore, using dedicated heatmaps, we show the sites where the two explorers collected specimens that were later identified as taxa new to science. These maps will also be useful to botanists, historians, scholars and curators of natural history museums, who work with Caucasian flora and vegetation, ethno-anthropology, history of photography, and landscape.